Penerapan Metode SAW Dalam Peringkat Hasil Pembelajaran Siswa SMK (STM) Berdasarkan Rekapitulasi Nilai - Rizka, Ade; Sari, Rahayu Mayang; Ulandari, Lavenia; Pratiwi, Daratika (Forum Kerjasama Pendidikan Tinggi, 2023)
Education and technology have a close relationship in their development. The process of implementing education has results that are indicators of success in the learning process. These results are the values that are processed or calculated based on the needs of each assessment. The value processing process will provide an overview of students' capabilities in understanding and mastering subjects. At the Panca Budi Medan Vocational School (STM) school, the value processing process is carried out without using a decision support system in the process of ranking student learning outcomes. The system used only performs value processing based on the presentation of student assessment components. So that teachers need a decision-making system that can help and facilitate the process, to avoid mistakes in ranking results and can save time. In this study, the SAW method is used as a multi-attribute decision support method in the process of ranking learning outcomes so that it can assist teachers in making decisions. Processing of value recapitulation comes from the assessment components, namely daily tests, midterm, and end of the semester from aspects of assessing students' knowledge and skills for each subject. The process of calculating the ranking of learning outcomes is carried out on sample data, namely 10 alternative students and 15 subject attributes in one class for one semester. The application of the SAW method and testing on sample data resulted in student ratings, namely alternative S5 with a value of 0.994 as the highest rank and S10 with a value of 0.908 as the lowest rank. Utilization of the system and application of the SAW method can help and make it easier for teachers to process grades and rank learning outcomes. So that based on the ranking results, teachers can improve the quality of teaching and provide solutions to deficiencies in the learning process